Benchmarking Eventually Consistent Distributed Storage Systems - Bermbach, David (KIT Scientific Publishing, 2014)
Cloud storage services and NoSQL systems typically offer only ""Eventual Consistency"", a rather weak guarantee covering a broad range of potential data consistency behavior. The degree of actual (in-)consistency, however, is unknown. This work presents novel solutions for determining the degree of (in-)consistency via simulation and benchmarking, as well as the necessary means to resolve inconsistencies leveraging this information.